Analisis Penegakan Hukum Terhadap Pelaku Tindak Pidana Kekerasan Dalam Rumah Tangga (KDRT) di Indonesia - Hartinah, Titin; Anwar Sadat (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This writing is motivated by the increasing crime rates, particularly Domestic Violence (KDRT), which is often caused by a lack of commitment, poor communication, and an inability to understand the dynamics of household problems. In many cases, women and children are the majority victims of Domestic Violence, resulting in harm both physically and psychologically. The impact of such violence is often severe and can even lead to death due to excessive violent actions. However, it is important to note that the victims of Domestic Violence are not limited to women and children. In Indonesia, men, including husbands who play the role of head of the household, as well as parents, both mothers and fathers, can also be victims of violence. Therefore, this writing aims to provide an understanding that Domestic Violence can involve various members of a household, and it is not always women or children who are the perpetrators or victims. This paper aims to find out how the law enforcement process and efforts made by law enforcement in dealing with law enforcement obstacles against perpetrators of Domestic Violence (KDRT) in Indonesia.